The optimization of zakat funds distribution in Aceh in improving the welfare of the disable - Juli Dwina Sari; Fahriansah; Sumarni (Prodi Manajemen Zakat dan Wakaf, Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Langsa, 2023)
Objectives – The purpose of this study was to determine the optimal level and implementation of the zakat fund distribution program for the Disabled within the perspective of improving the well-being of mustahik. Method – The descriptive qualitative research design is used in this study. In this study, there were five informants, two of whom were key figures. The primary and secondary data sources used in this study were observation, interviews, and documentation. Findings – The study's findings indicate that the distribution of zakat funds for disability has not been carried out optimally, and the funds are channeled through two program criteria, namely moderate disability and severe disability, and have not had a significant impact on improving the welfare of mustahik. Mustahik wishes for more programs, such as those that provide business capital to people with disabilities. Limitation– study only focused on Zakat Fund Compensation Program for the Disabled provided by Baitul Mal Aceh Tamiang regency. Practical Implication– This study demonstrates the need for additional disability compensation programs in Baitul Mal, Aceh Tamiang Regency, such as providing business capital to disabled people so that they can feel prosperous.